Análisis petrológico y estructural del basamento ígneo-metamórfico en la quebrada de agua negra, cordillera de San Buenaventura, Catamarca - Aciar, Rafael Hernán (2019)
The Cordillera de San Buenaventura forms a mountain range that extends from E-O to ESE-ONO and is located on the border between the Puna Austral and the Sierras Pampeanas. We analyze the petrology and the structure of the crystalline basement outcropping in the Agua Negra creek, located in the southern sector of the San Buenaventura range. This study determined that the area is constituted by mylonites, ultramilonites and granitoids without deforming. The deformation that affects the crystalline basement defines a ductile shear zone. The samples analyzed in thin section shows an intense recrystallization suggesting that the thermal conditions during the deformation were superior to 500 °C.